The ESC: The Dangerous By-Product of V(D)J Recombination - Smith, Alastair L.; Scott, James N. F.; Boyes, Joan (Frontiers in Immunology, 2019)
V(D)J recombination generates antigen receptor diversity by mixing and matching individual variable (V), diversity (D) and joining (J) gene segments. An obligate by-product of many of these reactions is the excised signal circle (ESC), generated by excision of the DNA from between the gene segments. Initially, the ESC was believed to be inert and formed to protect the genome from reactive broken DNA ends but more recent work suggests that the ESC poses a substantial threat to genome stability. Crucially, the recombinase re-binds to the ESC, which can result in it being re-integrated back into the genome, to cause potentially oncogenic insertion events. In addition, very recently, the ESC/recombinase complex was found to catalyse breaks at RSSs throughout the genome, via a “cut-and-run” mechanism. Remarkably, the ESC/recombinase complex triggers these breaks at key leukaemia driver genes, implying that this reaction could be a significant cause of lymphocyte genome instability. Here, we explore these alternate pathways and discuss their relative dangers to lymphocyte genome stability.